Preliminary Study on Some Blood Parameters of White Snook (Centropomus viridis) Broodstock Reared in Aquaculture Recirculating System (RAS) - Iris Adriana Hernández-López; Virginia Patricia Domínguez-Jiménez; Rosa María Medina-Guerrero; Rodolfo Lozano-Olvera; Oscar Basilio Del Rio-Zaragoza; Leonardo Ibarra-Castro; Juan Manuel Martínez-Brown; Emyr Saúl Peña-Marín (Fishes, 2025)
The white snook (Centropomus viridis) is an emerging aquaculture species with high market acceptance, exhibiting catadromous and protandric hermaphroditic characteristics in adulthood. This study aimed to preliminarily characterize certain hematological and biochemical parameters, as well as blood cell morphology, for identifying possible variations between sexes maintained under aquaculture recirculating system (RAS) conditions. The white snook broodstock was anesthetized with clove oil, and biometric values, as well as sex classification, were measured. Then, blood samples were collected from 14 females (7132 ± 1610 g) and 20 males (2200 ± 0.963 g) via caudal vessel puncture to analyze selected hematological parameters, blood biochemistry, and cellular morphology. Fulton’s condition factor (K) showed no differences between sexes, indicating a healthy fish status. Females showed significantly higher serum cholesterol, glucose, and triglyceride levels than males. Also, hematocrit (HCT) and mean corpuscular volume (MCV) were elevated in females. No sex-related differences were observed in red or white cell counts or in blood cell dimensions. Morphological characterization identified erythrocytes, thrombocytes, and three types of leukocytes: lymphocytes (small and large lymphocytes), neutrophils, and monocytes, with no eosinophils or basophils detected in either sex. These findings provide fundamental reference values for the hematological and biochemical profiles of C. viridis broodstock in captivity and highlight sex-specific differences relevant for reproductive and health monitoring. However, it should be considered that the sample size used to establish reference ranges for the species is small, so it is recommended to implement a monitoring plan for this and other broodstocks of this emerging species.